LI BAI AND HIS WORKS - Dr Swati Mishra (IJRDO- Journal of Educational Research, 2025)
Li Bai is one of the most renowned poets from the Tang Dynasty. He is considered one of the greatest poets not only in China but also in the history of Chinese literature and world literature. He wrote about nature, friendship, love, and emotions. The simplicity of his poems makes him very popular. Li Bai’s poems are a must-have part of different course syllabi covering Asian literature, Chinese literature, and sometimes even the history of the world. This paper explores the enduring connection people have with his poetry, examining why and how it continues to resonate even after so many years.